2019
DOI: 10.5194/acp-19-14431-2019
|View full text |Cite
|
Sign up to set email alerts
|

Long-term total OH reactivity measurements in a boreal forest

Abstract: Abstract. Total hydroxyl radical (OH) reactivity measurements were conducted at the second Station for Measuring Ecosystem–Atmosphere Relations (SMEAR II), a boreal forest site located in Hyytiälä, Finland, from April to July 2016. The measured values were compared with OH reactivity calculated from a combination of data from the routine trace gas measurements (station mast) as well as online and offline analysis with a gas chromatographer coupled to a mass spectrometer (GC–MS) and offline liquid chromatograph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 56 publications
2
24
0
Order By: Relevance
“…As pointed out in earlier publications (e.g. Boy et al, 2006;Praplan et al, 2019), carbon monoxide (CO)…”
Section: Hydroxyl Radical -Ohmentioning
confidence: 84%
See 2 more Smart Citations
“…As pointed out in earlier publications (e.g. Boy et al, 2006;Praplan et al, 2019), carbon monoxide (CO)…”
Section: Hydroxyl Radical -Ohmentioning
confidence: 84%
“…At SMEAR II, monoterpenes are the dominant BVOCs (Bäck et al, 2012), and they are the major contributors to the OH reactivity of the measured organic compounds (Mogensen et al, 2015;Praplan et al, 2019). Thus, accurate modelling of monoterpenes is a crucial component for calculating the OH concentration.…”
Section: Validation Of Monoterpene Model Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is said that the studies of Sinha et al (2010) and Nölscher et al (2012) find missing reactivity in the boreal forest. Then you refer to Praplan et al (2019) who "recently demonstrated that including modelled oxidation products of VOCs that are not measured is not sufficient to explain the missing reactivity at the site". Please, make clear what site you are talking about here.…”
Section: Discussion Papermentioning
confidence: 99%
“…The reaction rate used in this study (1.2•10 −10 cm 3 s −1 , Atkinson et al, 1985) is, nevertheless, within the uncertainty of the value determined by Dillon et al, (1.28±0.1•10 −10 cm 3 s −1 ). While we did not discussed in detail uncertainty calculations in the original manuscript, we did in our previous publications (Praplan et al, 2017;2019), where we state that an uncertainty of 15 % is used for this reaction rate. p.5, l.122: The Comparative Reactivity Method (CRM) is used here for detecting the total OH reactivity with a gas chromatograph equipped with a PID.…”
Section: C5mentioning
confidence: 99%